2019
DOI: 10.1089/heq.2019.0056
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Primary Care After the Affordable Care Act: A Qualitative Study of Los Angeles Safety-Net Patients’ Experiences

Abstract: Purpose: Millions of people gained health care coverage in Los Angeles after the Affordable Care Act (ACA); however, challenges with obtaining and utilizing primary care still persist, particularly in the safety net. In this study, we explore barriers to accessing primary care services among safety-net patients in Los Angeles after Medicaid expansion and implementation of other programs for safety-net patients after the ACA. Methods: We conducted qualitative interviews, in Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 11 publications
1
25
0
Order By: Relevance
“…Primary care services may also be deprioritized by women on community supervision due to higher ranking daily needs, such as food and housing security (Dong et al, 2018), resulting in greater use of acute care services. In addition, a preference for emergency departments over other healthcare settings aligns with recent qualitative findings that Medicaid and public insurance enrollees described emergency departments and urgent care clinics as faster, cheaper, and more familiar than outpatient primary care settings (Saluja et al, 2019).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Primary care services may also be deprioritized by women on community supervision due to higher ranking daily needs, such as food and housing security (Dong et al, 2018), resulting in greater use of acute care services. In addition, a preference for emergency departments over other healthcare settings aligns with recent qualitative findings that Medicaid and public insurance enrollees described emergency departments and urgent care clinics as faster, cheaper, and more familiar than outpatient primary care settings (Saluja et al, 2019).…”
Section: Discussionsupporting
confidence: 71%
“…While legislation, such as the Affordable Care Act, has been enacted to increase insurance coverage among individuals recently released from incarceration or who are on community supervision (Bandara et al, 2015 ; Cuellar & Cheema, 2012 ; Knapp et al, 2019 ), improved insurance coverage has not sufficiently addressed gaps in outpatient service utilization rates among justice-involved individuals who have re-entered into the community and among the broader population of individuals on community supervision (Hawks et al, 2020 ; Saloner, Bandara, McGinty, & Barry, 2016 ). The continued underutilization of outpatient care among Medicaid enrollees has highlighted additional barriers to service use, such as perceived lack of coverage or unaffordable care, undervaluing primary care, length of time to first available appointment, and transportation (Saluja et al, 2019 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 Furthermore, studies have shown that one in five adults experience provider-related barriers both before and after reaching their primary care provider. 22,23 These barriers include difficulty scheduling appointments, lack of available physicians, unclear explanations, cost of services or drugs, insufficient coordination after the appointment, lack of early appointments, inadequate time spent by the provider with the patient, and type and cost of insurance coverage. Patients who experience one or more of these barriers are more likely to resort to emergency care.…”
Section: Disparities In Health Carementioning
confidence: 99%
“…[ 2 ] Research suggests that MMC enrolees face significant challenges in understanding their coverage and accessing primary care. [ 3 ]…”
mentioning
confidence: 99%